The Relationship Between Circulating Growth Differentiation Factor 15 Levels and Diabetic Retinopathy in Patients With Type 2 Diabetes - Niu, Yixin; Zhang, Weiwei; Shi, Jie; Liu, Yueming; Zhang, Hongmei; Lin, Ning; Li, Xiaoyong; Qin, Li; Yang, Zhen; Su, Qing (Frontiers in Endocrinology, 2021)
OBJECTIVE: Growth differentiation factor 15 (GDF15) is a member of the TGF-β superfamily with anti-inflammatory property. The objective of this study is to evaluate the relationship between plasma GDF-15 levels and diabetic retinopathy (DR) in patients with type 2 diabetes. MATERIALS/METHODS: A case-control study was performed with 402 patients with type 2 diabetes. Of these, 171 patients had DR and 231 were controls. The plasma GDF-15 levels were measured using ELISA methods. DR was diagnosed by the canon ophthalmic digital imaging system and the Canon EOS 10D digital camera (Canon, Tokyo, Japan) through a nonpharmacologically dilated pupil. RESULTS: The GDF-15 levels were significantly increased in patients with DR (168.9 [112.9-228.3] pg/ml vs. 127.8 [96.1-202.8] pg/ml, P<0.001) compared to controls. Spearman correlation analysis showed that the GDF-15 levels were positively associated with duration, FPG, SBP, ACR, Scr, and liver enzymes, and negatively associated with eGFR (both P < 0.001). The participants in the highest GDF-15 quartile had a significantly increased risk for DR (OR = 2.15, 95% CI 1.53-3.02) after adjusting for potential cofounders. CONCLUSIONS: The plasma GDF-15 levels are positively associated with DR independent of potential cofounders.